A frequency-dependent variable-damping control based variable-orifice damper for smart base-isolation system. (1st December 2022) - Li, Zhong-Xian; Wen, Dongbin; Shi, Yundong; Wei, Xin
Abstract: Damping devices are commonly used in the isolation layer of base-isolated structures to provide additional damping to control the structural responses. Normally, large damping for the isolation layer is useful to minimize the resonance effect under low-frequency ground motions, and small damping is preferred to reduce the structural responses under high-frequency ground motions. Traditional passive dampers are widely adopted in engineering practice. Due to the fixed damping characteristic, however, the performance of base-isolated structures with passive dampers cannot stay optimal under ground motions with different frequency characteristics. To realize an optimal control of base-isolated structures, semi-active control has been increasingly valued for its efficiency and intelligence to adjust the damping characteristics based on feedback information from the structure and ground motion. However, a large number of sensors and hardware components are required for semi-active control, which makes the system complex and costly. In this paper, a variable-orifice damper (VOD) for smart base-isolation system is proposed. The VOD can adaptably adjust its damping according to the frequency of the ground motion without additional power or sensors. Theoretical analysis and sinusoidal excitation tests were carried out to investigate the behavior of VOD. A series of numerical simulations of a base‐isolated structure equipped with the proposed VOD and subjected to ground motions are also conducted. A semi-active control with ON-OFF strategy, and two passive controls (passive-on and passive-off) are conducted for comparison. The simulation results show that the VOD can result in an optimal control under ground motions with different frequency characteristics.